7.4 PSYCHOTIC EXPERIENCES IN CHILDHOOD AND SUBSEQUENT SUICIDAL BEHAVIOR IN ADOLESCENCE – A COPENHAGEN CHILD COHORT 2000 STUDY. (9th April 2019) - Rimvall, Martin K; van Os, Jim; Rask, Charlotte Ulrikka; Olsen, Else Marie; Clemmensen, Lars; Munkholm, Anja; Skovgaard, Anne Mette; Verhulst, Frank; Jeppesen, Pia
Abstract: Background: The rates of non-suicidal self-injury (NSSI) and suicidal behaviors have increased markedly in youth populations worldwide; and suicide is among the leading causes of death in patients recently diagnosed with psychotic disorders. In general population samples of children and youth, well replicated findings report a strong association between psychotic experiences (PE) and NASSI and suicidal behaviors. However, most studies on youth are cross-sectional and few have adjusted for confounding factors such as other psychopathology, in particular depression. The current study aims to examine the longitudinal associations between PE and NSSI and suicidal behaviors during adolescence. We anticipated that especially individuals with persistent PE from childhood would be at increased risk of NSSI and suicidal behaviors 5 years later in adolescence. Methods: The current study examined a total of 1, 138 youth from the general population cohort, the Copenhagen Child Cohort 2000, who were examined at age 11 years and followed up at age 16 years. PE and depressive symptoms were assessed by clinical interviews at age 11 using the Kiddie Schedule of Affective Disorders and Schizophrenia. At follow-up, PE were assessed by the self-report measure, the Psychosis-Like Symptom Interview, and depressive symptoms were assessed using the Mood and Feelings Questionnaire. NSSI and suicidal behaviors during the last year were also assessed by self-report at age 16. Using multinomial logistic regression analyses, the risk rate ratios (RRR) of NSSI, suicidal ideation and suicide attempt at age 16 were calculated for remittent PE (only at age 11), incident PE (only at age 16) and persistent PE (at both measurement occasions), crude, and after adjustment for depressive symptoms at either time-point. Results: PE at ages 11 and 16 years were strongly associated with suicide attempts within the last year at age 16: For remittent PE RRR=8.1 (95%CI 1.3–49.4), incident PE RRR=12.8 (3.2–51.9), persistent PE RRR=23.7 (4.6–121.6). After adjustment for depressive symptoms the associations were reduced substantially: remittent PE RRR=5.6 (95%CI 0.9–36.6), incident PE RRR=5.2 (1.2–23.5), persistent PE RRR=9.0 (1.5–52.3). The same overall patterns were found for NSSI and suicidal ideation. For NSSI: remittent PE RRR=1.9 (1.0–3.6), incident PE RRR=3.1 (2.0–4.9), persistent PE RRR=4.9 (2.4–9.6). After adjustment for depressive symptoms: remittent PE RRR=1.5 (95%CI 0.8–3.0), incident PE RRR=1.8 (1.1–2.9), persistent PE RRR=2.5 (1.1–5.6). For suicidal ideation: remittent PE RRR=1.6 (0.9–2.8), incident PE RRR=4.5 (3.1–6.5), persistent PE RRR=4.0 (2.1–7.6). After adjustment for depressive symptoms: remittent PE RRR=1.3 (95%CI 0.7–2.5), incident PE RRR=3.0 (1.9–4.5), persistent PE RRR=2.1 (1.0–4.6). Conclusions: PE at age 11 years mark an increased risk of NSSI and suicidality at 16 years, especially if PE persist. All associations between PE and NSSI and suicidality were markedly reduced after adjusting for depressive symptoms, however holding significance for both incident and persistent PE. The remaining association is likely, at least in part, due to residual confounding. However, even if PE might not play a direct causal role in NNSI and suicidal behaviors in youth, they can still be regarded as important markers of vulnerability and severity that are easily assessed and hence clinically useful in the assessment of children and youth.